PELATIHAN COREL DRAW UNTUK PERANGKAT DESA NGAWONGGO KECAMATAN TAJINAN - Harianto, Wahyudi; Wiguna, Anggri Sartika (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Ngawonggo Village is one of the villages in Tajinan subdistrict, Malang Regency, a suburb of Malang. Technology for rural communities is a thing that is still rather rarely used so that the village apparatus. The need for knowledge of fundamental technology as a support in all village activities is still lacking, the primary requirement for graphic design that is somewhat large will support all village activities. Community service currently carried out in the Village Administration Environment, especially in Ngawonggo Village, T Handicraft District. Images of banners, banners, business cards, and other things expected after this training, village officials can create attractive communication media with billboards, banners, and others for information about the village community.